Personality dimensions and attitudes towards peace and war. Issue 1 (9th January 2017) - Blumberg, Herbert H.; Zeligman, Ruth; Appel, Liat; Tibon-Czopp, Shira
Abstract : Purpose: The purpose of this paper is to examine the relationship between major personality dimensions and attitudes towards peace and war. Design/methodology/approach: Three samples – two consisting of British psychology students ( n =64 and 121) and one of Israeli students ( n =80), responded to measures of some or all of: five-factor inventory, SYMLOG trait form, general survey including authoritarianism; attitudes towards peace and war; specific attitudes towards peace and war policy. Findings: The general attitude measures were associated with the specific attitudes. Both were associated with authoritarianism but not consistently with other personality dimensions. Research limitations/implications: Descriptive findings might not generalize and need contextualization. Authoritarianism should be measured in any studies of attitudes related to peace, war, conflict, and structural violence. Practical implications: Practitioners of peace education may first need to address high authoritarianism and low integrative complexity. Also, countering structural violence related, for instance, to poverty or prejudice/discrimination may require a comprehensive approach including collaborative work with clinical psychologists applying both implicit and explicit assessment tools. Originality/value: Documenting links (and lack of them) among personality variables and attitudes towards peace and war has practical and theoretical value – and may contribute to organizational schemes shaped by personality structure and bearing implications for negotiations. In terms of a paradigm by Morton Deutsch, our results show individual differences in, and associations among, variables relating to the remediable likelihood of parties being differentially likely to find themselves in negatively vs. positively interdependent situations; and carrying out effective instead of "bungling" actions.